Countering the counterfeiters - Venkataraman, Ray R., (SAGE Knowledge. Cases., 2017)
This case describes the negative impacts of counterfeiting in the health care industry. The costs of local supplier counterfeiting must be taken into account when manufacturers make location decisions in developing their overseas supply chain. The case illustrates the complexity in making global location planning decisions.